Bibliometric Behavior of Green Consumers - Loso Judijanto (Westscience Press, 2026)
The growing global emphasis on sustainability has intensified scholarly interest in understanding green consumer behavior and its role in promoting environmentally responsible consumption. This study aims to map the intellectual structure, thematic evolution, and collaborative landscape of research on green consumer behavior through a bibliometric analysis. Using data retrieved from the Scopus database, the study applies VOSviewer to analyze keyword co-occurrence, overlay visualization, density mapping, co-authorship networks, institutional collaboration, and country collaboration patterns. The results reveal that the literature is strongly centered around core themes such as sustainability, sustainable development, and consumer behavior, indicating a mature research foundation that integrates environmental awareness with marketing and economic perspectives. Temporal analysis shows a shift from early studies focusing on attitudes and perceptions toward emerging topics related to energy efficiency, green computing, and technological innovation, reflecting the growing influence of digital transformation within sustainability discourse. Collaboration analysis highlights the dominant role of Asian countries, particularly China and India, alongside contributions from the United States and European nations, suggesting an increasingly global research landscape. Despite its growth, the field remains somewhat fragmented, emphasizing the need for stronger interdisciplinary and international collaboration. Overall, this study provides a comprehensive overview of the evolution and future trajectory of green consumer behavior research, offering theoretical insights and practical implications for researchers, policymakers, and industry practitioners seeking to advance sustainable consumption practices.